Variability of the Southwestern Patagonia (51°S) Winds in the Recent (1980–2020) Period: Implications for Past Wind Reconstructions - Carolina Gómez-Fontealba; Valentina Flores-Aqueveque; Stéphane Christophe Alfaro (Atmosphere, 2022)
The Southern Hemisphere Westerly Winds (SWW) control the amount and latitudinal distribution of rainfall in southwestern Patagonia. Recent studies have shown that SWW has intensified in the last decades, but their past behavior is not yet well understood. To understand this behavior, it is necessary to analyze climatic data from meteorological stations and reconstruct their variability through paleoclimatic evidence, such as lake cores. Nevertheless, Patagonia is an austral region characterized by its complex topography and quasi lack of a meteorological network. In this work, three reanalyses are studied (MERRA-2, ERA5, and GLDAS) and compared with the Cerro Castillo and Teniente Gallardo stations (~51°S), with the aim of simulating the winds in the past. The results indicate that ERA5 and MERRA-2 simulate well the wind variability in the study region, while GLDAS is less reliable. Therefore, the first two reanalyses could be used to extend the time series of the meteorological station and calibrate a new wind proxy based on the abundance and size of the aeolian particles, reconstructing in a direct way the intensity of the SWW in the past over southwestern Patagonia.